2005
DOI: 10.2151/jmsj.83a.121
|View full text |Cite
|
Sign up to set email alerts
|

Amount and State of Mineral Particles in the Upper Mixed Layer and the Lower Free Troposphere over Mt. Raizan, Southwestern Japan: Unmanned Airplane Measurements in the Spring of 2003

Abstract: The number fractions of mineral particles mixed with sea salt of all the mineral particles in the mixed layer were much higher than those in the free troposphere. These results suggest that mineral particles mixed with sea salt were formed in the marine boundary layer. The weather record suggests that the formation process through the clouds, which has previously been considered an efficient formation process for mixed particles, cannot explain sufficiently the observed abundance of mineral particles internall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Mineral dust particles over East Asia may be modified and become internally mixed particles through the adsorption of gases or coagulation with other kinds of aerosol particles during their transport. The internally mixed particles of dust and sea salt were often found in the boundary layer over Japan in the spring and its fraction often exceeded 80% of total dust particles (e.g., Zhang et al 2003Zhang et al , 2006Yamashita et al 2005). Although it is possible that the CCN ability of the mineral dust particles changes with such modifications, few studies have addressed this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Mineral dust particles over East Asia may be modified and become internally mixed particles through the adsorption of gases or coagulation with other kinds of aerosol particles during their transport. The internally mixed particles of dust and sea salt were often found in the boundary layer over Japan in the spring and its fraction often exceeded 80% of total dust particles (e.g., Zhang et al 2003Zhang et al , 2006Yamashita et al 2005). Although it is possible that the CCN ability of the mineral dust particles changes with such modifications, few studies have addressed this issue.…”
Section: Discussionmentioning
confidence: 99%
“…During the ADEC IOPs, analyses were made using a Scanning Electron Microscope with an EnergyDispersive X-ray analyzer (SEM-EDX) for samples collected at Dunhuang (a dust source region), Beijing and Nagoya (central Japan; Iwasaka et al, 2003b;Matsuki et al, 2005), and at Mt. Raizan (southwestern Japan; Yamashita et al, 2005).…”
Section: Mixing Of Dust Aerosol During Long-range Transportationmentioning
confidence: 99%
“…A positive correlation was also found with the number of sulfate containing particles and the relative humidity. Yamashita et al (2005) carried out an in situ sampling of aerosol particles from 800 to 2000 m altitude over Mt. Raizan (33.5°N, 130.2°E) from March to April 2003 using an unmanned radio-controlled airplane.…”
Section: Mixing Of Dust Aerosol During Long-range Transportationmentioning
confidence: 99%
“…A simple calculation indicated that the Brownian coagulation time of 1 µm dust particles with ∼2 µm sea-salt particles was about 2.6 weeks (i.e., much longer coagulation time compared to the lifetime of dust particles) (the coagulation time is defined as the time for the initial number concentrations of the dust particles to decrease by half, and the initial number concentrations of the dust particles and sea-salt particles are assumed to be 1,000 and 100 #/cm 3 , respectively) (Hinds 1999;Baron and Willeke 2001). However, the possibility of direct coagulation of dust particles and sea-salt particles cannot be completely ruled out (Zhang et al 2003;Yamashita et al 2005).…”
Section: Hygroscopicity and Volatility Of Ad Particlesmentioning
confidence: 99%